2003
DOI: 10.1152/japplphysiol.00879.2002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced exercise arteriovenous O2difference in Type 2 diabetes

Abstract: Maximal O(2) consumption (Vo(2 max)) is lower in individuals with Type 2 diabetes than in sedentary nondiabetic individuals. This study aimed to determine whether the lower Vo(2 max) in diabetic patients was due to a reduction in maximal cardiac output (Q(max)) and/or peripheral O(2) extraction. After 11 Type 2 diabetic patients and 12 nondiabetic subjects, matched for age and body composition, who had not exercised for 2 yr, performed a bicycle ergometer exercise test to determine Vo(2 max), submaximal cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
69
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 35 publications
10
69
0
3
Order By: Relevance
“…The a−vO 2 , calculated using the Fick equation and measured cardiac output and oxygen uptake, is lower during exercise in adult type 2 diabetic patients [5], but not in diabetic adolescents. Baldi et al [5] found that a−vO 2 was lower during exercise in type 2 diabetic adults and postulated that impaired endothelial function may have effected a maldistribution of blood to exercising muscle.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The a−vO 2 , calculated using the Fick equation and measured cardiac output and oxygen uptake, is lower during exercise in adult type 2 diabetic patients [5], but not in diabetic adolescents. Baldi et al [5] found that a−vO 2 was lower during exercise in type 2 diabetic adults and postulated that impaired endothelial function may have effected a maldistribution of blood to exercising muscle.…”
Section: Discussionmentioning
confidence: 85%
“…Baldi et al [5] found that a−vO 2 was lower during exercise in type 2 diabetic adults and postulated that impaired endothelial function may have effected a maldistribution of blood to exercising muscle. In contrast, we found that a−vO 2 was the same in diabetic as in non-diabetic adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes Care 2014;37:143937: -144637: | DOI: 10.233737: /dc13-2031 Exercise is a standard recommendation in the management and prevention of type 2 diabetes mellitus (T2DM) (1,2). Regrettably, people with diabetes often have reduced cardiac reserve (3,4) and a resultant decrease in aerobic capacity (3,5). Adults with T2DM have smaller left ventricular stroke volume (6) and reduced heart rates (3,7) during peak exercise.…”
mentioning
confidence: 99%
“…В то же время, в исследовании J.C. Baldi и соавт. [3] не выявлено различий между показателями максимального сердечного выброса у диабетиков и лиц без диабета, сопоставимых по уровню физи-ческой активности, индексу массы тела и возрасту. В данной работе выявлено снижение максимальной артерио-венозной разницы по содержанию кислорода на 19% в сравнении с груп-пой контроля.…”
unclassified